SMART STREET LIGHT BASED ON VEHICLE DETECTION (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The main objective of this project is to develop an embedded system which switches or turn ON the light by detecting the vehicles on the road for energy saving of street light.Whenever IR sensor is detected it just indicates the Arduino to switch on the street lights. Then lights are switched on till the vehicle leaves and switches off automatically.Another way to this approach is, one can maintain minimum intensity without completely switching off the lights by using PWM and switch them on to maximum intensity whenever it detects the vehicle. But in this article the circuit is designed in such a way that lights are completely switched OFF and will be switched ON only when there is any vehicle.This device can also be used for turning on and turning off the street lights based on the climate of the weather. When it is day the street lights automatically gets turned off by detecting the sun rays i.e High intensity. Whenever the sensor finds the low intensity i.e night time it automatically turns on the street lights. Based on the intensity the brightness of the light also varies using PWM. So it can be used for multiple purposes with the slight changes in it.